Recomendação de fertilizantes para Eucalyptus saligna Sm. com base no balanço nutricional na região de Guaíba - RS - Witschoreck, Rudi (2014)
This research conducted in different ages of Eucalyptus saligna Sm. stands in the region of Guaíba - RS, had as objectives: to estimate and model the biomass production; to estimate the nutrients stock and calibrate a fertilization recommendation system of soil based on the nutritional balance. On the basis of the forest inventory, trees of medium diameter were collected and fractionated in leaf, branch, bark, wood and root. The accumulated litter was evaluated with sampling units of 1 m2. Samples of arboreal components and litter were collected to estimate the dry matter and nutritional content. The modeling of biomass correlated dendrometric variables with the biomass of components trees and the accumulated litter. The biomass per unit area was estimated through the product between the average dry matter of each component and the number of trees per hectare, and in the case of accumulated litter, based on area of sample units. The net primary productivity was calculated accounting for the successive increments of biomass above and below ground and litter fall. Nutrients stock was obtained through the product between the average biomass of each component and the average concentration of nutrients. The fertilization recommendation system of soil was established considering the demand of nutrients according to the expected productivity and the supply of nutrients in the soil. Considering the average of stands of different ages, the main components in biomass accumulation were: wood > root > bark > branch > leaf. In relative values, only wood showed increasing trend with age of stands. The net primary productivity in stands between 2 and 8 years of age was 40.3 Mg ha-1 year-1, and 80 % in the components above ground and 14 % below ground. For the average of stands, the stock of nutrients showed the following order of accumulation: wood > root > leaf > bark > branch; and for nutrients: Ca > N > K > Mg > P ~ S > Fe > Mn > B > Zn > Cu. The fertilization recommendation system for Eucalyptus saligna based on the nutritional balance was shown efficient in determining doses of fertilizers, estimating values increased with the reduction of soil fertility and the increase of production expected. Based on the fertilizer recommendation system was possible to establish the following order of probability of nutritional limitation productivity: P > K > N > Ca ~ Mg, in Eucalyptus saligna plantations.